PERANCANGAN SISTEM INFORMASI PELAYANAN DAFTAR USULAN PENETAPAN ANGKA KREDIT SECARA ONLINE BERBASIS WEBSITE DIREKTORAT JENDERAL PELAYANAN KESEHATAN KEMENTERIAN KESEHATAN - Nuryadi, Hepi; Gardenia, Yulisa (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2020)
ABSTRACTDevelopment of a service information system on the list of proposals for determining credit points online based on a website. Service information system list of credit score determination proposals (Simpadu) is a system used to track or monitor DUPAK file management (list of credit score determination proposals) health functional positions at the Directorate General of Health Services conducted through the Integrated Services Unit (ULT) and this is strengthened with the DUPAK Circular Letter dated 4 - May - 2015, in the context of improving the quality of service and orderly administration in the process of Determining Functional Credit Score in the Health sector. This research is a type of Applied Research. The information system development method uses the Prototype model. The method of data collection is done by observation, data sampling, literature study, and interviews. The method used in analyzing and designing a system is the Object Oriented Analysis and Design method using Unified Modeling Language (UML). The results of this research are in the form of software in the form of website Information Systems list service of determining credit numbers that can serve to provide information on the management of DUPAK files. Keywords:     Information Systems service list of proposals for determining credit points, DUPAK, Prototype, Object-Oriented Analysis and Design.